HUBUNGAN USIA PENYAPIHAN DAN POLA KONSUMSI SUSU FORMULA DENGAN KEJADIAN KARIES GIGI PADA ANAK BALITADI DESA MRANGGEN SUKOHARJO - PERMATASARI, DINA, Endang Nur W, S.St., M.Si.Med, Toto Suharto, SKM., M.Kes (2015)
DEPARTMENT OF NUTRITION SCIENCE FACULTY OF HEALTH SCIENCE MUHAMMADIYAH UNIVERSITY OF SURAKARTA BACHELOR THESIS ABSTRACT DINA PERMATASARI. J310110048 RELATIONSHIP BETWEEN AGE OF WEANING AND FORMULA CONSUMPTION PATTERNS AND DENTAL CARIES AMONG CHILDREN IN MRANGGEN VILLAGESUKOHARJO. Introduction:Dental caries cavities are the most common tooth decays in children. Dental caries are due to loss of minerals from email , dentin , and cementum. Dental caries can be caused by several factors, such as early feeding and consumption patterns of infant formula, due to fermentation of carbohydrates. Objective:This study aimed to assess the relationship between age of weaning and formula consumption patterns and dental caries in children in the village of Sukoharjo Mranggen. Research method:This research was an observational with cross sectional design. Subjects were toddlers aged 24-59 monthsof Mranggen, Sukoharjo. Sampling technique usedsimple random sampling technique. Statistical tests used Chi - Square tests. Results:The study showed most children had dental caries (59,6%). Most children were weaned at the right age (88,5%). Most children consumed formula in a big amount (51,9%). There was 61,5% children consumed formula rarely. Most children consumedformula in morning, noon and night (57,7%). Most children consumed formula in short diration (86,5%). Conclusion:No relationship between weaning age and dental caries in under five children under five in the village of Mranggen,Sukoharjo.No relationship between formula consumption pattern and dental caries in under fivechildren in the village of Mranggen, Sukoharjo. Keywords:weaning age, formula consumption patterns, dental caries Bibliography:69:1993-2013